PENGARUH FAKTOR EKSTERNAL, INTERNAL DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR DI BANJARMASIN - Purboyo; Nuril Huda (Universitas Lambung Mangkurat, 2017)
Customers purchasing products is the main goal of marketing, so that factors that influence purchasing decisions are important to be known. This study aims to analyze factors that influence motorcyle purchasing decisions. It is hypothesized that external factors, internal factors and lifestyle influence motorcyle purchase decisions. The population used in this research was motorcycle buyers in the city of Banjarmasin. 150 respondents were taken as samples using a non-probability sampling technique with a purposive sampling approach. The analysis technique used in this research is a structural equation model (SEM) and the hypothesis is tested by using statistical analysis with 18.0 AMOS program. The results of this study indicate that (1) external factors have direct and significant effect on purchasing decisions; (2) internal factors have direct and significant effect on lifestyle; (3) internal factors influence the purchase decision through lifestyle; and (4) lifestyle has direct and significant effect on purchasing decisions. Based on the research results, it is suggested that external factors have the most dominant direct influence toward the purchasing decisions and the variables that have highest index are marketing activities with dimensions of price, product, promotion, and marketing place, so that the variable of the marketer should focus and pay deeper attention to the marketing strategies, but still considering the external and internal factors. Lifestyle factor with the indicators of activities, interest, and opinions have a strong influence to the purchasing desicion. This can help companies to match suitable products that are going to be sold with the lifestyle of the consumers